Methods and means to improve the efficiency thermal processing of solid fuel in a fluidized bed - Semenenko, Ye.V.; Dyakun, I.L. (Геотехнічна механіка, 2015)
Problems of improving a fluidized bed technology by way of pulsing air (gas) fed into the bed are considered. A model of and calculation procedure for rational parameters of the coal particles pulsating flowing, moving and firing in the fluidized bed as well as empirical dependence of efficiency of gassing process during combustibles firing in the bed are proposed, which take into account operation parameters of the pulsating fluidized bed. Physics of impact of amplitudefrequency characteristics of the air pulsating feed on the completeness of the coal particles burningout in the bed was investigated. It is stated that the pulsations period T = 0.5 – 2 s and porosity = 0,3 - 0,4 are rational parameters as they increase rate of solid fuels burning-out in the pulsed fluidized bed by 20 - 40% if compared with stationary bed. Technical facilities (pulsators) were designed, which feed pulsing air into the fluidized bed and provide controllable air stream pulse shapes and pulse ratio.